HUBUNGAN PERKEMBANGAN MENTAL-EMOSIONAL TERHADAP SIBLING RIVALRY PADA ANAK PRESCHOOL - Muhammad Roni Septiawan (Jurnal Vokasi Keperawatan (JVK), 2022)
The socio-emotional development of preschool-aged children aims for children to have the ability to control emotions with their environment, this causes the need for situation adjustments, especially for preschoolers to avoid social jealousy and a sense of competition among siblings (sibling rivalry). This study aims to determine the relationship of mental-emotional development to sibling rivalry in preschool children. This study aims to determine the relationship of mental-emotional development to sibling rivalry in preschool children. The research design used was descriptive correlational using a cross sectional approach. The sample used in this study were 98 parents who have preschool age children using purposive sampling technique. The measuring instrument used is a mental-emotional problem questionnaire (KMME) and a sibling rivalry questionnaire which have been tested for validity and reliability. The results of the detection based on the KMME were 62 children (63.2%) were in the category of the possibility of children experiencing mental-emotional problems and 58 children (59.2%) were in the high category based on the sibling rivalry questionnaire. The results of this study indicate that 54 children who experience mental-emotional problems who experience the possibility of mental-emotional problems (31.9%) will experience sibling rivalry in preschool children (p value 0.000 with 0.05). The results of this study can be concluded that there is a significant relationship between mental-emotional development and sibling rivalry in preschool children. Research recommends that parents seek more information and knowledge about their children's mental-emotional development, so as to minimize sibling rivalry in their children.